Changes in Typhoon Activities and Regional Precipitation Variability over the Korean Peninsula according to Different Phases of El Niño - Jong-Suk Kim; Sun-Kwon Yoon; Sang Myeong Oh; Young-Il Moon (Advances in Meteorology)
We analyzed typhoon activities such as tropical cyclone (TC) genesis position, movement routes and central pressure of typhoons, and changes in local patterns of rainfall stemming from TCs passing through the Korean domain. The results showed a remarkable difference in changes in typhoons that affect the Korean Peninsula (KP) during cold tongue (CT) and warm pool (WP) El Niño years. In particular, TCs that move through the ocean off Korea and the Kuroshio during WP El Niño years are relatively stronger than TCs formed during CT El Niño years. Furthermore, analysis of large-scale atmosphere-ocean dynamics showed better conditions for TC development and strengthening during WP El Niño years. TC-induced summer rainfall over major Korean river basins decreased from normal years during CT El Niño years (−3.94%) and increased over normal years during WP El Niño years (+33.92%). The results of this diagnostic study rely on short-term observations and relatively little data, but they suggest that CT/WP El Niño cycles influence TC activities and rainfall across the KP. The findings are important for reducing TC damage and ensuring a proper response to climate change in coupled human-environmental systems.